Conn Syndrome –A Rare Entity Presenting As Periodic Paralysis – An Even Rarer Presentation. - Amitoj Singh; Manavjot Kaur; Vikas Chander; Ajay Pal; Pankush Kansal; Ajey bhaskar (GMC Patiala Journal of Research and Medical Education, 2020)
Conn’s syndrome presents with hypertension with hypokalemia. Hypokalemic Periodic Paralysis is another rare disease with genetic defect resulting in loss of function mutation in SCN4A sodium channel in muscle(1). Between the attacks of weakness , potassium values are normal in patients in hypokalemic periodic paralysis but remain low in secondary hypokalemia.(2) Here we report a case of primary aldosteronism where disease presented with hypokalemic periodic paralysis.